The Problem of Mind-Body Dichotomy: A Critique of the Cartesian Approach - Mendie, John Gabriel; Nwanaokuo, Udofia, Stephen (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
The mind-body problem is a perennial philosophical problem that seeks to uncover the relationship or causal interaction that exists between the corporeal and incorporeal aspects of the human person. It thrives under the assumption that the human person is made up of two distinct entities, that is, mind and body, which explains their assumed causal relation. As attractive as this may seem, not all philosophers agree to this feigned idea of interaction and bifurcation of the human person. One philosopher of note, who sorts to address this problem in the 17th century, is René Descartes. For Descartes, minds and bodies are distinct kinds of substances, where bodies are spatially extended substances (a res extensa) and minds are unexpended substances characterised primarily by thought (a res cogitans). But, if minds and bodies are radically dissimilar, how could they causally interact? This paper, therefore, attempts to examine the philosophical foundations of Cartesian dualism. It also articulates the major arguments adopted by Descartes through his methodic doubts to address the mind-body problem. The paper concludes by highlighting some fundamental criticisms of Cartesian Interactionism in the light of recent trends in parapsychology and neuroscientific research.